Hippocampal Dot Sign in Transient Global Amnesia: A Neurologist’s Experience - Anandan, Somarajan; Rajendran, Sajeesh S.; Danworapong, Wananwat; Sarojam, Manoj Krishnan; Alexander, John (Nepal Journal of Neuroscience, 2024)
Transient global amnesia, coined by Fisher and Adams, is characterized by a sudden, complete inability to retain new information, lasting for several hours, in a middle-aged or older person, with preservation of alertness and all other cognitive functions. It affects 3 to 10 persons per 100,000 people. It has a benign prognosis with low rates of recurrence. MRI brain taken during the episode is often normal and often shows dot like diffusion restriction in hippocampus when MRI brain is taken 24 to 72 hours after the ictus. Presence of hippocampal dot sign is helpful in confirming the diagnosis of TGA and ruling out the usual differential diagnosis.